The outcomes and impact of community seed banks: Findings from Kenya and Uganda - Vernooy, Ronny; Otieno, Gloria; Adokorach, Joyce (2024)
To assess the outcomes and impact of the community seed bank work by the Alliance in East Africa, in the second half of 2023, we carried out a participatory evaluation study of 3 community seed banks in Kenya and 4 in Uganda, of the 12 that the Alliance established in both countries (4 in Kenya, 8 in Uganda). The study had two complimentary parts: 1) the community seed bank by numbers (# of crops and varieties conserved, # of farmer beneficiaries, seed sales, other sales), and 2) the community seed bank by outcomes, covering 5 areas (seeds, agriculture, livelihood, social organization and empowerment, and security and resilience).